Pengelolaan Kelas Sebagai Acuan Pembelajaran Aktif: Array - Athalia A. Aptanta Tumanggor; Neviyarni; Herman Nirwana (eductum: Jurnal Literasi Pendidikan, 2022)
Learning is a process of interaction between students and educators, also known as teachers. From the implementation of learning activities in the classroom, there is having problems and obstacles faced by a teacher will be definitely found. So it must be appropriately handled carefully by the teacher. Therefore, it is important for teachers to understand how to manage the class well, because basically the problems that arise. Classroom management is a conscious effort to plan, organize, actualize, and supervise programs and activities in class, so that learning occurs may be systematic, effective and fun way.